2017
DOI: 10.1371/journal.pone.0171025
|View full text |Cite
|
Sign up to set email alerts
|

A targeted gene expression platform allows for rapid analysis of chemical-induced antioxidant mRNA expression in zebrafish larvae

Abstract: Chemical-induced oxidative stress and the biochemical pathways that protect against oxidative damage are of particular interest in the field of toxicology. To rapidly identify oxidative stress-responsive gene expression changes in zebrafish, we developed a targeted panel of antioxidant genes using the Affymetrix QuantiGene Plex (QGP) platform. The genes contained in our panel include eight putative Nrf2 (Nfe2l2a)-dependent antioxidant genes (hmox1a, gstp1, gclc, nqo1, prdx1, gpx1a, sod1, sod2), a stress respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…2 A , 3 A ). In general, cell response to Cu started earlier at 4 h and lasted till 24 h. In contrast, cell response to Cd started later at 12 h and lasted longer till 48 h. In one study, the expression of zsod1 , zsod2 and zgst showed no change, was suppressed and was induced, respectively, in zebrafish larvae after 3-h Cd exposure [ 61 ]. This result is similar to the 4-h Cd exposure result in our study.…”
Section: Discussionmentioning
confidence: 99%
“…2 A , 3 A ). In general, cell response to Cu started earlier at 4 h and lasted till 24 h. In contrast, cell response to Cd started later at 12 h and lasted longer till 48 h. In one study, the expression of zsod1 , zsod2 and zgst showed no change, was suppressed and was induced, respectively, in zebrafish larvae after 3-h Cd exposure [ 61 ]. This result is similar to the 4-h Cd exposure result in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of hepatic genes involved in the cellular antioxidant response and mitochondrial function were quantified in fish from the dietary exposure laboratory study using a customized Quantigene® plex 2.0 (QGP) panel (Affymetrix, Fremont, CA) (Mills and Gallagher, 2017). The antioxidant response genes included glutamate-cysteine ligase catalytic subunit ( GCLC ), phospholipid hydroperoxide glutathione peroxidase (GPx4), and mitochondrial superoxide dismutase (SOD2).…”
Section: Methodsmentioning
confidence: 99%
“…To investigate if Cr, As, Cd and Zn share a similar mechanism of olfactory toxicity through whole larval oxidative stress, targeted gene expression was performed. Analysis of eight putative Nrf2 (Nfe2l2a)-dependent antioxidant genes (hmox1 a, gstp1, gclc, nqo1, prdx1, gpx1a, sod1, sod2), a stress response gene (hsp70), an inducible DNA damage repair gene (gadd45bb), and three reference genes (actb1, gapdh, hprt1) was completed after 24 hr metal exposures using the QuantiGene Plex (QGP) assay following procedures described in Mills & Gallagher (2017). In addition, a second QGP assay was developed that targeted two homologs of metallothionein (mt2 and mtbl) and contained two reference genes (actb1, and hprt1) and that was analyzed using the same protocol.…”
Section: Methodsmentioning
confidence: 99%